Mapeo genético y análisis de QTL para carotenos en una población S1 de yuca - Marín Colorado, JA; Ramírez, H.; Fregene, Martin A. (2009)
The S1 population of the Thai variety MTAi8 (AM320), which shows patterns of segregation defined by the content of total carotenes (beta-carotene), underwent an analysis of segregating bulk (BSA = Bulk segregating Analysis) using 700 molecular markers type microsatellites or SSR. There were generated 25 tying groups and identifying 3 major QTLs associated with a region of the genome of cassava with the content of total carotenes. Three markers SSR; explained the 37.2% (NS109), 32% (rSSRY251) and 27.7% (rSSRY313) of the total phenotypic variance, placed in the Group D strongly tying, associated with the content of total carotenes in the family AM320 S1, which established a strong positive correlation between color and content root pulp carotenes total (r = 0.81), and between negative and carotenes total dry matter (r = -0.31). The three possible QTLs showed positive and additive effect for the content of totals carotenes and could be an opportunity to implement assisted selection markers for total carotenes in cassava.